1991
DOI: 10.1037/0882-7974.6.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Visual/cognitive correlates of vehicle accidents in older drivers.

Abstract: Older drivers have more accidents per miles driven than any other age group and tend to have significant impairments in their visual function, which could interfere with driving. Previous research has largely failed to document a link between vision and driving in the elderly. We have taken a comprehensive approach by examining how accident frequency in older drivers relates to the visual/cognitive system at a number of levels: ophthalmological disease, visual function, visual attention, and cognitive function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
282
1
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 429 publications
(304 citation statements)
references
References 29 publications
(49 reference statements)
10
282
1
5
Order By: Relevance
“…Mean (standard deviation) driving performance [59, 65,66]. Indeed, visuo-attentional disorders and reduction of the size of the visual field of view have been shown to be associated with a higher crash risk [59,65,66]. In these articles, the crash rate during the five years preceding the visual attention evaluation was associated with the test performances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean (standard deviation) driving performance [59, 65,66]. Indeed, visuo-attentional disorders and reduction of the size of the visual field of view have been shown to be associated with a higher crash risk [59,65,66]. In these articles, the crash rate during the five years preceding the visual attention evaluation was associated with the test performances.…”
Section: Discussionmentioning
confidence: 99%
“…Performances in the UFOV® test are associated with crash risk and also road (26) 60 (18) 48 (12) 58 (18) Sub-scores Visual attention 19 (4) 25 (5) 20 (4) 25 (6) Interaction with other road users 6 (4) 7 (4) 5 (3) 7 (4) Planning 13 (7) 14 (6) 11 (5) 11 ( CT cognitive training, CT + DS cognitive training + driving simulator experience. Mean (standard deviation) driving performance [59, 65,66]. Indeed, visuo-attentional disorders and reduction of the size of the visual field of view have been shown to be associated with a higher crash risk [59,65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Though driving a vehicle is shown to be a highly visual dependent task, a number of studies have shown that there is no clear relationship between visual acuity and driving performance (Ball et al, 1993;Decina & Staplin, 1993;Gresset & Meyer, 1994;Hills, 1980;Ivers et al, 1999; Johansson et al, 1996;Marottoli et al, 1994;McCloskey et al, 1994;Owsley et al, 1998;Owsley et al, 1991;Shinar & Schieber, 1991). However, some other tasks such as reading road signs and avoiding obstacles in the roadway, are found to be affected by visual acuity loss (Higgins et al, 1998).…”
Section: Visual Acuity and Driving Performancementioning
confidence: 99%
“…Health concerns linked to unsafe driving in older drivers include chronic physical conditions (Dobbs, Caprio Triscott, & McCraken, 2004;Marottoli, Cooney, Wagner, Doucette, & Tinetti, 1994), visual attention and processing deficits (Ball & Owsley, 1991, 1996, and age-related cognitive decline and dementia (Cooper, Tallman, Tuokko, & Beattie, 1993;Dobbs, Heller, & Schopflocher, 1998;Johansson et al, 1996;McKnight & McKnight, 1999). As the percentage of older drivers in the population increases it is becoming increasingly important to have reliable and valid assessment tools to assess driving ability in this group.…”
Section: Introductionmentioning
confidence: 99%
“…On-road driving assessments are generally used as the "gold standard" measure of driving safety and often serve as the dependent variable in studies attempting to find predictors of driving safety. However, it has also been suggested that on-road assessments act as proxies for more critical measures, such as adverse driving outcomes in real-world driving situations (Owsley, Ball, Sloane, Roenker, & Bruni, 1991).…”
Section: Introductionmentioning
confidence: 99%